2013
DOI: 10.3390/nu5103854
|View full text |Cite
|
Sign up to set email alerts
|

Cocoa and Heart Health: A Historical Review of the Science

Abstract: The medicinal use of cocoa has a long history dating back almost five hundred years when Hernán Cortés’s first experienced the drink in Mesoamerica. Doctors in Europe recommended the beverage to patients in the 1700s, and later American physicians followed suit and prescribed the drink in early America―ca. 1800s. This article delineates the historic trajectory of cocoa consumption, the linkage between cocoa’s bioactive-mechanistic properties, paying special attention to nitric oxides role in vasodilation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 93 publications
0
7
0
1
Order By: Relevance
“…The Kuna are one of few remaining tribes who are protected from vascular ailments, such as arterial hypertension (Corti et al, 2009 ). It has been suggested that this is due to the prominent role cocoa plays in the Kuna diet (Galleano et al, 2009 ; Hollenberg et al, 2009 ), where they consume the equivalent of five cups of liquid cocoa, or approximately 900 mg cocoa flavanols, per day (Pucciarelli, 2013 ). Research demonstrated that when members of the Kuna relocated to Panama, changing their culture and diet (in particular a reduced dietary intake of flavanol-rich cocoa), significant increases in blood pressure were subsequently observed (Galleano et al, 2009 ; Fraga et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Kuna are one of few remaining tribes who are protected from vascular ailments, such as arterial hypertension (Corti et al, 2009 ). It has been suggested that this is due to the prominent role cocoa plays in the Kuna diet (Galleano et al, 2009 ; Hollenberg et al, 2009 ), where they consume the equivalent of five cups of liquid cocoa, or approximately 900 mg cocoa flavanols, per day (Pucciarelli, 2013 ). Research demonstrated that when members of the Kuna relocated to Panama, changing their culture and diet (in particular a reduced dietary intake of flavanol-rich cocoa), significant increases in blood pressure were subsequently observed (Galleano et al, 2009 ; Fraga et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly various phytoextracts and their active principles have shown to provide effective cardioprotection against various challenges [42][43][44][45][46][47][48][49][50]. Cocoa consumption has been previously linked to cardiac health and various mechanisms have been proposed for the cardioprotective effects of cocoa [51]. TMP is one of the major bioactive component of cocoa liquors and in Chinese black vinegar [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…This evergreen tropical crop has been cultivated in more than 50 countries in the world due to its benefit to the chocolate, confectionery and cosmetic industries 2 . Likewise, the medicinal benefits of cocoa were noted recently 3 . In addition, cocoa is often grown in agroforestry-type ecosystems alongside other fruit and commodity crops so the plantation of this fruit tree has provided sustainable economic and environmental benefits in many countries 4 .…”
Section: Introductionmentioning
confidence: 94%